Online supported learning and threshold concepts in novice programming - Sim, Tze Ying * (2017)
Novice programming is a challenging subject to both the students and the educators. Students struggle to comprehend the methods, and educators try their best to put forth the subject in an understandable manner. This paper presents two methods implemented to support the learning for students in a novice programming class. They are social network support and online journaling. The threshold concepts for computing are also discussed. Data collected through the online journaling method provides an indicator to the possible threshold concepts in novice programming subject. The impacts of the methods are evaluated using analysis of questionnaires responds, entries to the social networking support platform, online journaling method, and students’ grade. The conclusion of this study are 1) the social support network helps students to work on the subject content, and 2) students who post on the platform have a significantly better grade. The conclusion drawn for the online journaling are 1) students who actively participated are scoring better grade in the class, and 2) online journaling method also confirms that one of the main thresholds for novice programming class is the object oriented concept. Apart from Memory and Object Oriented Programming, Multidimensional array and Methods are another two topics identified as threshold concepts for novice programming.